ISO 14001 certification: analysis of the factors related to the employees awareness to the environmental of a paper industry on the center – south region of Paraná - Crotti, Katiane; Maçaneiro, Marlete Beatriz; Kuhl, Marcos Roberto (Revista de Administração da UFSM, 2017)
Environmental management systems certified by NBR ISO 14001:2004 emerge as alternatives for organizations to structure their environmental activities. The certification requires a primordial factor, which is environmental awareness. Given this, this research aims to identify and analyze the factors related to the environmental awareness of employees included in the ISO 14001 certification process, on a paper industry of the Center-South region of Paraná. In order to achieve the proposed objectives, we applied a quantitative approach by the application of questionnaires to the employees of the industry researched. The treatment of the data occurred by means of descriptive statistics, being used the parameters of average, standard deviation and coefficient of variation, as well as the factor analysis for grouping and analysis of factors that showed more awareness and testing validation of the scale. As a result, they identified the factors related to environmental awareness, which were passed on to the employees by training, internal disclosures and other mechanisms that helped the company to achieve a satisfactory level of awareness. However, there was an opportunity for the paper industry to enhance awareness to waste management, wastewater and chemicals, since not all employees know the destination and the treatment of waste at the end of process.